Arthropathy in Dressler's syndrome. Issue 663 (January 1981) - Davidson, C.
Abstract : Three patients developed a polyarthritis in association with Dressler's (post-myocardial infarction) syndrome. Joint involvement was more pronounced in the upper limbs and persisted many months after other features of Dressler's syndrome had settled. In 2 cases the findings in the joints were slight and might have been overlooked but for the persistently raised ESR. There was a prompt symptomatic response to prednisone.